Escherichia coli Triggers Intestinal Inflammation and Mucosal Damage Through Immune Activation: Escherichia coli Memicu Peradangan Usus dan Kerusakan Mukosa Melalui Aktivasi Kekebalan Tubuh - Mohammed I. Hammood; Jawad N. K. Makassees (Academia Open, 2025)
General Background: The intestinal mucosa plays a crucial role in immune defense and homeostasis. Specific Background: Pathogenic Escherichia coli (E. coli) infection disrupts this balance, triggering immune responses and inflammation. Knowledge Gap: The detailed immune mechanisms underlying E. coli infection, including cytokine production and immune cell infiltration, remain poorly understood. Aims: This study investigates the immune responses, cytokine production, and mucosal damage induced by E. coli infection. Results: Using murine models and clinical samples, E. coli infection resulted in elevated cytokine levels (TNF-α, IL-6, IL-1β), increased immune cell infiltration (neutrophils, macrophages, T cells), and mucosal damage, such as reduced villus height and increased crypt depth. Novelty: This research provides comprehensive insights into the immunological and histopathological consequences of E. coli infection, integrating cytokine analysis, immune profiling, and tissue damage assessment. Implications: The findings highlight potential therapeutic targets for preserving intestinal mucosal integrity and reducing systemic inflammation. Future studies should focus on exploring molecular mechanisms and developing interventions to mitigate the impact of E. coli infections. Highlights: E. coli disrupts intestinal mucosa, triggering immune responses and inflammation. Investigate immune responses, cytokine production, and mucosal damage due to E. coli. Elevated cytokines, immune cell infiltration, and mucosal damage highlight systemic inflammation. Keywords: E. coli, immunity, intestine